Progress in structural engineering, mechanics and computation : proceedings of the second International Conference on Structural Engineering, Mechanics and Computation, 5-7 July 2004, Cape Town, South Africa /: proceedings of the second International Conference on Structural Engineering, Mechanics and Computation, 5-7 July 2004, Cape Town, South Africa. (2014) - Unknown
No abstract available